Orientação religiosa, valores pessoais e intenção empreendedora: evidências empíricas no Brasil e em Portugal - Sousa, Evangelina da Silva (2020)
The field of research on entrepreneurship allows for the expansion of investigations that integrate other fields of research with Business Administration, such as its intersection with religion. To understand the connection between religion and the entrepreneurial mindset leads to the investigation of the value system that shapes individual actions and, in turn, influences the economic process. Thus, the objective of this research was to analyze the influence of religious orientation in the values of self-promotion and openness to change and in the background of the entrepreneurial intention of university students, using the Theory of Human Values, proposed by Schwartz (1992), and the Theory of Planned Behavior, outlined by Ajzen (1991). To this end, descriptive, quantitative research was carried out with university students from the Business Administration major at the Federal University of Ceará (Brazil) and university students from the Management and Economics at the University of Minho (Portugal). The instrument used in data collection was developed by adapting three scales validated in the literature: Portrait Values Questionnaire (SCHWARTZ, 2001), Age Universal 'IE Scale-Revised (GORSUCH; MCPHERSON, 1989) and Entrepreneurial Intention Questionnaire (LIÑÁN; CHEN, 2009). Techniques for statistical analysis of the data were used, such as descriptive statistics and equation modeling based on partial least squares adjustment estimation models. The results showed that the entrepreneurial intention of Brazilian and Portuguese students is influenced by religious orientation, by the attitude favorable to entrepreneurship and by the perceived control of entrepreneurship. Through the chi-square Q test, significant associations between some sociodemographic variables (country of origin, gender, religious affiliation, and entrepreneurial family members) and educational variables (school period, curricular component, complementary training in entrepreneurship and professional expectation after completion) were verified graduation) in the entrepreneurial intention of Brazilian and Portuguese students. Also, religious orientation and subjective norms for the recognition of entrepreneurship influenced the favorable attitude towards entrepreneurship and the perceived control of entrepreneurship by Brazilian and Portuguese students. In general, the results contribute to the existing literature on entrepreneurship, by adding religious orientation as one of the antecedents of entrepreneurial intention, in addition to reinforcing the Theory of Planned Behavior, proposed by Ajzen (1991), as a suitable theoretical model for measure intention, which is manifested from beliefs, motivations, and values, including religious orientation, giving an innovative character to this study, in addition to the possibility of conducting future research.